Pengaruh Kepercayaan , Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan melalui Kepuasan sebagai Variabel Intervening pada Bengkel AHASS (Studi kasus pada pelanggan Bengkel Ahass Cabang Wendit) - Kisvidatul Hikmah; M. Hufron; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract               This study aims to determine the effect of Trust, Service Quality and Price on Customer Loyalty through Satisfaction as an Intervening Variable for customers of Ahass Workshop, Wendit Branch. Population and sample are customers of Ahass Workshop, amounting to 83 customers. The data collection technique used in this study is to use a questionnaire or questionnaire data collection method. The tool used for data analysis in this study is to use a software application in the form of SPSS version 20. The method of analysis in this study uses path analysis. Path analysis or path analysis is the development of a multiple linear regression analysis model that is used to test the influence of intervening variables. The results of this study indicate that trust, service quality and price have a direct effect on satisfaction, trust and price have a direct effect on loyalty, while service quality has no direct effect on loyalty, and satisfaction has a direct effect on loyalty, trust has a direct effect on loyalty through satisfaction as a variable. mediation, service quality affects loyalty through satisfaction as a mediating variable, price affects loyalty through satisfaction as a mediating variable. Keywords: trust, service quality, price and loyalty satisfaction